Association between microRNA 671 polymorphisms and the susceptibility to soft tissue sarcomas in a Chinese population - Zhang, Peng; Li, Xinling; Huang, Lingling; Hu, Fulan; Niu, Xiaoying; Sun, Yang; Yao, Weitao (Frontiers in Oncology, 2022)
The study aimed to evaluate the association between the microRNA (miRNA) gene polymorphisms and the susceptibility to Soft tissue sarcomas (STSs). In this case-control study, DNA was extracted from leukocytes in peripheral blood which was collected from 169 STSs patients and 170 healthy controls. Three SNPs for miR210, five SNPs for miR206, two SNPs for miR485, two SNPs for miR34B, two SNPs for miR671, three SNPs for miR381 were investigated and genotyped usinga Sequenom Mass ARRAY matrix-assisted laser desorption/ionization-time of flight mass spectrometry platform. Unconditional logistic regression analysis was used to analyze the association between miRNA gene polymorphisms and the susceptibility to STSs. The results showed that miR-671 rs1870238 GC+CC (OR =1.963, 95%CI = 1.258-3.064, P = 0.003) and miR-671 rs2446065 CG+GG (OR =1.838, 95%CI = 1.178-2.868, P = 0.007) may be a genetic risk factor of STSs after adjustment for age and smoking. Therefore, this study suggests that individuals carrying the GC+CC genotype for miR-671 rs1870238 or the CG+GG genotype for miR-671 rs2446065 may be susceptible to STSs.